QHAPAQ ÑAN: THE INCA ROAD AND TERRITORIAL TRANSFORMATION IN THE PERUVIAN ANDES - Martínez Martínez, Guadalupe (2010)
Qhapaq Ñan was the main artery of a widespread road network built in the Andes in the days of the Inca Empire and which connects nowadays territories belonging to six countries. This road expressed a form of conceiving and handling the territory that has undergone intense historical changes, although some of its parts have kept alive its value and functionality to the present time. Its protection and its conservation go beyond the monumental and archaeological dimension involving the territorial management from a conception that takes into account both the cultural heritage and the cultural landscape.